THE ROLE OF SHARIA COOPERATIVES IN IMPROVING THE ECONOMY AND WELFARE OF PEOPLE IN INDONESIA - Nabilla Risdayani; Nadra Sagita; Siti Mardhiah; Sri Nabilah (Cahaya Ilmu Bangsa Institute, 2023)
Sharia cooperatives have an important role in improving the economy and welfare of people in Indonesia. This study aims to analyze the role of sharia cooperatives in improving the economy and community welfare. The research methods used are literature studies and field observations. The results showed that sharia cooperatives play a role in people's economic empowerment, poverty alleviation, job creation, and income equality. Sharia principles applied by sharia cooperatives such as justice, help, and partnership have helped improve the welfare of members and the surrounding community. Policy recommendations provided include increasing sharia financial literacy for the community and funding support for the development of sharia cooperatives.